A Detailed Kinetic Model for the Methanol Oxidative Dehydrogenation on Vanadia-Based Catalysts: Aggregation State Role and Active Site Requirements - Santander-Meyer, R (Elsevier B.V., 2024)
A kinetic model was derived for the methanol oxidative dehydrogenation to formaldehyde, methyl formate and dimethoxymethane on sub-monolayer and multilayer V2O5/TiO2 catalysts. Considering a hemiacetal intermediate, the model combines Langmuir-Hinshelwood/Eley-Rideal/Mars-van Krevelen mechanisms, accounting for lattice oxygen redox sites and Brønsted acid sites. The fitted model depends on 4 thermodynamically consistent parameters, adequately simulating yield trends with temperature, residence time, and partial pressure of methanol, oxygen and added water. Oxidation steps follow a Mars-van Krevelen redox cycle, while the dimethoxymethane formation is reversible, as the water addition favored the hemiacetal intermediate. The catalyst with higher vanadia surface density was intrinsically more active (lower activation energy of the rate limiting step), attributed to its higher reducibility, while showing weaker methanol adsorption (lower enthalpy of chemisorption). The increase in reducibility correlates with the transition from monomers to polymers to crystalline vanadia when vanadium content increases, as observed by XRD, Raman spectroscopy and DRS-UV–vis. © 2024 Elsevier B.V.